Validity and between-unit agreement of commercially-available linear position transducer and inertial sensor devices during loaded countermovement jumps - Tredrea, M. S. J.; Clarke, A. C.; Middleton, K. J.; Bourne, M. N.; Carey, D. L.; Scanlan, A. T.; Dascombe, B. J. (Sports Biomechanics, 2022)
To assess the validity and between-unit agreement of velocity monitoring devices during incrementally-loaded countermovement jumps (CMJ), 16 males (24.0 ± 3.5 yr) completed 12 CMJs on a force plate (FP). Performance variables were collected through two linear position transducers (GymAware [GA]) and four accelerometer-based devices (two PUSH units, two Bar Sensei units). Pearson correlations (r) and coefficients of variation (CV) demonstrated strong to very-strong relationships (r = 0.60-0.88) and poor agreement (CV = 11.7-25.3%) between FP and GA, and moderate to very-strong relationships (r = 0.31-0.81) and poor agreement (CV = 10.1-24.2%) between FP and PUSH. Between-unit comparisons demonstrated moderate to very-strong relationships (r = 0.50-0.88) with poor agreement (CV = 10.8-26.6%) for GA, and very weak to very-strong relationships (r = 0.01-0.87) with moderate to poor agreement (CV = 9.1-24.1%) for PUSH. Bar Sensei units were excluded from analyses. Loaded CMJ data collected with either device displayed poor agreement with a FP. Velocity monitoring devices demonstrate poor validity across all loads; however, GA demonstrated strong between-unit agreement. A FP should be utilised to accurately assess CMJ performance at all times.